High internal phase Pickering emulsions stabilized by plant protein and polysaccharide composite particles: Construction, stability, application, and research advance - Qianqian Gu; Zhengxue Li; Yaran Fan; Yang Tan; Jiannan Yan; Chengbin Zhao; Jingsheng Liu (Food Hydrocolloids, 2026)

Targeted degradation of aromatic pollutants in complex matrices via selective electrocatalytic O2 activation to 1O2 over O-doped Fe single-atom catalysts - Danyu Zhang; Qingquan Liu; Yuchen Wang; Tingli Yang; Wei Wang; Gang Liao; Hao Zhang; Miao Guo; Haifang Tang; Chengbin Liu (Water Research, 2026)

SOC1 clade genes coordinate lateral root development and response to multiple phytohormonal and environmental stress signals in Arabidopsis - Xinyue Li; Qian Ma; Ping Jin; Yaxuan Wang; Tongyao Yang; Ying Chen; Shujuan Guo; Zisheng Zhang; Chengbin Xiang; Qiuling Wang; Linhui Yu (Journal of Plant Physiology, 2026)

Hydroxyl-enriched cerium oxide-chitosan hybrid macroporous beads for arsenite deep removal: Batch and column adsorption - Ting Wang; Maosong Zhao; Ran An; Kong Yang; Yuanfeng Wei; Jie Luo; Chengbin Liu; Xiaolong Liu; Kai Yin (Chemical Engineering Journal, 2026)

Point discharge molecular emission spectrometer as a highly sensitive GC detector for the analysis of furans in food products - Yuan Yang; Xiaoli Wu; Qiuyi Yan; Hongling Zhou; Yurong Deng; Chengbin Zheng (Food Chemistry, 2025)

Oxygen-poisoning induces disproportionation in Zr0.8Nb0.2Co0.6Cu0.2Ni0.2 hydrogen storage alloy - Haoyu Wang; Jiacheng Qi; Shiting Yang; Jing Gu; Miaogen Chen; Chengbin Zhang; Chao Li; Zhendong Yao (Chemical Engineering Journal, 2025)

Biocompatible chitosan-assisted green-synthesized AgNPs-PSPAE nanoplatform for synergistic antimicrobial and anti-inflammatory therapy in infected wound healing - Yuxin You; Jiamin Li; Fructueux Modeste Amona; Luyuan Yang; Yijia Yang; Xinyi Liu; Chengbin Shi; Ziqi Sha; Yanzhu Li; Fangxu Bu; Lixuan Cao; Yuxi Zhou; et al. (Chemical Engineering Journal, 2025)

IQGAP1 participates in bone marrow-derived macrophage recruitment and involves in liver inflammation/fibrosis - Na Chang; Yuehan Ma; Jing Liu; Weiyang Li; Jing Zhao; Yuran Liu; Fuquan Liu; Chengbin Dong; Chang Liu; Changbo Qi; Lin Yang; Liying Li (Journal of Molecular Medicine, 2025)

Verification method for formation control of USVs based on virtual-real integration - Changdong Yu; Zhihao Zhang; Xuyang Liu; Chengbin Yang; Yizhuo Wang; Xiao Liang (Ocean Engineering, 2025)

Pollution levels, distribution characteristics and risk assessment of heavy metals (HMs) in road dust in major cities of China - Naibing Liang; Chengbin Zhang; Yuying Zhang; Nan Jiang; Jiajia Yang; Ningbo Geng; Ruiqin Zhang; Haijun Zhang; Jiping Chen (Journal of Hazardous Materials, 2025)

All-in-one detecting dairy iodine based on single drop microextraction coupled with ratiometric fluorescence filter effect - Ruiqi Gao; Simin Ye; Xiaofang Yang; Ying Zhang; Yuanyuan Liu; Jinyi Zhang; Chengbin Zheng (Food Chemistry, 2025)

Boosted toxicity reduction and deep removal of As(III) over porous Fe-doped Co3O4 nano brush-like array anode: Trade-off between electrocatalytic activity and adsorption capacity - Huiling Liu; Weijian Yang; Yuanfeng Wei; Yufen Xia; Haifang Tang; Zhifei Zheng; Chengbin Liu (Journal of Hazardous Materials, 2025)

An RGB difference prior for aerial remote sensing image dehazing with a DCP enhancement learning network - Jianchong Wei; Kunping Yang; Yi Wu; Chengbin Chen (International Journal of Remote Sensing, 2025)

In vitro and in vivo anti-osteoporotic effects of different fractions from Xanthoceras sorbifolium wood - Dandan Wu; Xinyue Yang; Qianqian Xu; Zhiwei Yao; Chengbin Shan; Haiyan Xu; Chaomei Ma (Natural Product Research, 2025)

Monocular vision-based key feature point positioning method for micro-vibration measurement of building structures - Wang Xie; Ming Yang; Guanghui Tan; Ying Wang; Chengbin Liang; Deguang Wang (Engineering Structures, 2025)

Quantum particle swarm optimization with chaotic encoding schemes for flexible job-shop scheduling problem - Yuanxing Xu; Deguang Wang; Mengjian Zhang; Ming Yang; Chengbin Liang (Swarm and Evolutionary Computation, 2025)

Effect of silver nanoparticles on biological nitrogen removal in sequential batch wastewater treatment process: Microbial communities, functional genes, and interactions - Yuliang Zhu; Hui Zhang; Hongwei Sun; Yan Zhang; Lei Yang; Chengbin Liu; Xinyi Yang; Yucan Liu (Journal of Water Process Engineering, 2025)

Genome-Wide Identification, Characterization, and Expression Analyses of the Mucin Genes in Japanese Flounder (Paralichthys olivaceus) - Ying Zhu; Xinsheng Yang; Xu Yan; Ning Yang; Min Cao; Chengbin Gao; Chao Li (Journal of Ocean University of China, 2024)

3D printed microplasma optical emission spectrometry coupled with ZIF-8 based dispersive solid-phase extraction for field analysis of waterborne arsenic - Jiahui Yang; Yao Lin; Xi Wang; Yuanyuan Li; Yurong Deng; Chengbin Zheng (Analytica Chimica Acta, 2024)

Dielectric barrier discharge-induced chemical vapor generation for highly sensitive analysis of iodine in seawater by ICP-MS - Yuke Wu; Jiahui Yang; Yurong Deng; Jinyi Zhang; Chengbin Zheng (Analytica Chimica Acta, 2024)

Assessment of total mercury in urban particulate matter by filter fiber assisted matrix solid-phase dispersion coupling with microplasma assisted-cold vapor generation - Qing Tan; Yuan Yang; Linshan Yang; Dandan Wang; Xiaoling Hou; Kerage Dorothy Mokeira; Jialun Wu; Guibin Lv; Shuxia Xu; Chengbin Zheng (Analytica Chimica Acta, 2024)

Risk assessment and spatial analysis of paralytic shellfish toxin (PST) concentrations and acute dietary exposure of commercially available shellfish in coastal areas in China - Shuwen Li; Jiao He; Jinfang Sun; Feng Pan; Pingping Zhou; Lei Zhang; Xin Yang; Chengbin Cao; Xiaojin Yu; Pei Cao (Food Control, 2024)

Arsenic field test kits based on solid-phase fluorescence filter effect induced by silver nanoparticle formation - Wenhui Yang; Liqing Ye; Yuke Wu; Xi Wang; Simin Ye; Yurong Deng; Ke Huang; Hong Luo; Jinyi Zhang; Chengbin Zheng (Journal of Hazardous Materials, 2024)

Effect of ultrasound on heated soybean isolate protein-soybean oligosaccharide glycation conjugate acid-induced emulsion gels and their applications as carriers of zeaxanthin - Zejun Chu; Xinqi Li; Runzhi Han; Qi Yang; Peng Fei; Hao Zhang; Yuzhu Wu; Xiuying Xu; Chengbin Zhao; Jingsheng Liu (Food Hydrocolloids, 2024)

AIEgens-enhanced rapid sensitive immunofluorescent assay for SARS-CoV-2 with digital microfluidics - Yuping Zeng; Xiangyu Gan; Zhourui Xu; Xiaoxiang Hu; Chenxuan Hu; Hanbin Ma; Hangjia Tu; Bao Chai; Chengbin Yang; Siyi Hu; Yujuan Chai (Analytica Chimica Acta, 2024)

Unsupervised structural damage assessment method based on response correlations - Yonghui Lu; Liqun Tang; Chengbin Chen; Licheng Zhou; Zejia Liu; Yiping Liu; Zhenyu Jiang; Bao Yang (Engineering Structures, 2024)

Accumulation characteristics of metals in human breast milk and association with dietary intake in northeastern China - Chengbin Zhang; Yun Luo; Shuai Sun; Tian Tian; Meiwen Zhu; Zia Ahmad; Jiajia Yang; Jing Jin; Haijun Zhang; Jiping Chen; Ningbo Geng (Science of The Total Environment, 2024)

Performance enhancement of ice storage capsules by biomimetic fins - Liangyu Wu; Jie Yu; Junjun Yang; Wei Gao; Chengbin Zhang; Cheng Yu (International Journal of Refrigeration, 2024)

Systematical Evaluation of the Structure-Cardiotoxicity Relationship of 7-Azaindazole-based PI3K Inhibitors Designed by Bioisosteric Approach - Tianze Wu; Yi Chen; Chengbin Yang; Mingzhu Lu; Fang Geng; Jianhua Guo; Yan Pi; Yun Ling; Jun Xu; Tong Cai; Lei Lu; Yaming Zhou (Cardiovascular Toxicology, 2023)

Probabilistic Back Analysis Based on Adam, Bayesian and Multi-output Gaussian Process for Deep Soft-Rock Tunnel - Jiancong Xu; Chengbin Yang (Rock Mechanics and Rock Engineering, 2023)

Deep remediation of As(III) in water by La-Ce bimetal oxide modified carbon framework - Yuanfeng Wei; Jing Zhao; Weijian Yang; Zhiyuan Qiu; Yufen Xia; Zhimin Wang; Yuxin Li; Chengbin Liu (Journal of Hazardous Materials, 2023)

Identification and functional characterization of caspases in turbot (Scophthalmus maximus) in response to bacterial infection - Tong Cui; Peng Liu; Xuan Chen; Zhe Liu; Beibei Wang; Chengbin Gao; Zhongyi Wang; Chao Li; Ning Yang (Fish & Shellfish Immunology, 2023)

Reconstruction of long-term strain data for structural health monitoring with a hybrid deep-learning and autoregressive model considering thermal effects - Chengbin Chen; Liqun Tang; Yonghui Lu; Yong Wang; Zejia Liu; Yiping Liu; Licheng Zhou; Zhenyu Jiang; Bao Yang (Engineering Structures, 2023)

Reconstruction of structural long-term acceleration response based on BiLSTM networks - Yonghui Lu; Liqun Tang; Chengbin Chen; Licheng Zhou; Zejia Liu; Yiping Liu; Zhenyu Jiang; Bao Yang (Engineering Structures, 2023)

Probing the deep brain: Enhanced multi-photon imaging by aggregation-induced emission luminogens via nanocrystallization - Zhourui Xu; Xiangquan Deng; Gang Feng; Wanjian Zhang; Yibin Zhang; Wenguang Zhang; Miaozhuang Fan; Mengni Hu; Chengbin Yang; Ming Ying; Yuanyuan Shen; Weixin Xie; et al. (Chemical Engineering Journal, 2023)

Microbial degradation of petroleum characteristic pollutants in hypersaline environment, emphasizing n-hexadecane and 2,4 di-tert-butylphenol - Shiling Liu; Wenjiao Yuan; Xiaolin Yang; Chengbin Li; Yishan Ji; Xin Feng; Meitong Li; Yuhong Xie (Environmental Monitoring and Assessment, 2023)

Rapid and sensitive quantification of cyclamate in beverages by miniature microplasma optical emission spectrometry - Jiang Jing; Siyu He; Jiahui Yang; Rui Yang; Yao Lin; Chengbin Zheng (Food Chemistry, 2023)

Synergistic influence of ultrasound and dietary fiber addition on transglutaminase-induced peanut protein gel and its application for encapsulation of lutein - Chengbin Zhao; Fang Wang; Xinbiao Yang; Yuxuan Mao; Qi Qi; Mingzhu Zheng; Xiuying Xu; Yong Cao; Yuzhu Wu; Jingsheng Liu (Food Hydrocolloids, 2023)

Genome-wide identification and functional characterization of inhibitor of nuclear factor-κB (IκB) kinase (IKK) in turbot (Scophthalmus maximus) - Zhe Liu; Peng Liu; Tong Cui; Xuan Chen; Beibei Wang; Chengbin Gao; Zhongyi Wang; Chao Li; Ning Yang (Fish & Shellfish Immunology, 2023)

Mass transfer enhancement of air sparging on VOCs contaminated low-permeability soil by establishing pressure gradient - Long Xu; Xinyi Hu; Fusheng Zha; Heyong Kang; Lixing Fang; Bo Kang; Chengfu Chu; Chengbin Yang (Chemosphere, 2023)

Tumor-targeting gene-photothermal synergistic therapies based on multifunctional polydopamine nanoparticles - Ying Zhang; Shiqi Tang; Xiaoyun Feng; Xiang Li; Jingyu Yang; Qiqi Liu; Meirong Li; Yujuan Chai; Chengbin Yang; Suxia Lin; Jia Liu (Chemical Engineering Journal, 2023)

Accumulation and distribution characteristics of rare earth elements (REEs) in the naturally grown marigold (Tagetes erecta L.) from the soil - Chengbin Zhang; Ningbo Geng; Yubing Dai; Zia Ahmad; Yun Li; Shuai Han; Haijun Zhang; Jiping Chen; Jiajia Yang (Environmental Science and Pollution Research, 2023)

Comparative Transcriptome Analysis of Spleen Reveals Potential Regulation of Genes and Immune Pathways Following Administration of Aeromonas salmonicida subsp. masoucida Vaccine in Atlantic Salmon (Salmo salar) - Qiang Fu; Yuqing Li; Hao Zhang; Min Cao; Lu Zhang; Chengbin Gao; Xin Cai; Defeng Chen; Ziying Yang; Jie Li; Ning Yang; Chao Li (Marine Biotechnology, 2022)

A community effort to assess and improve computerized interpretation of 12-lead resting electrocardiogram - Zijian Ding; Guijin Wang; Huazhong Yang; Ping Zhang; Dapeng Fu; Zhen Yang; Xinkang Wang; Xia Wang; Zhourui Xia; Chiming Zhang; Wenjie Cai; Binhang Yuan; et al. (Medical & Biological Engineering & Computing, 2022)
Computerized interpretation of electrocardiogram plays an important role in daily cardiovascular healthcare. However, inaccurate interpretations lead to misdiagnoses and delay proper treatments. In this work, we built a high-quality Chinese 12-lead resting electrocardiogram dataset with 15,357 records, and called for a community effort to improve the performances of CIE through the China ECG AI Contest 2019. This dataset covers most types of ECG interpretations, including the normal type, 8 common abnormal types, and the other type which includes both uncommon abnormal and noise signals. Based on the Contest, we systematically assessed and analyzed a set of top-performing methods, most of which are deep neural networks, with both their commonalities and characteristics. This study establishes the benchmarks for computerized interpretation of 12-lead resting electrocardiogram and provides insights for the development of new methods.

Probing the Molecular-Level Interactions in an Active Pharmaceutical Ingredient (API) - Polymer Dispersion and the Resulting Impact on Drug Product Formulation - Fengyuan Yang; Yongchao Su; James Small; Chengbin Huang; Gary E. Martin; Andrew M. Farrington; James DiNunzio; Chad D. Brown (Pharmaceutical Research, 2020)

Assessment of strength and leaching characteristics of heavy metal–contaminated soils solidified/stabilized by cement/fly ash - Fusheng Zha; Chunjie Ji; Long Xu; Bo Kang; Chengbin Yang; Chengfu Chu (Environmental Science and Pollution Research, 2019)

Dynamics of MiRNA Transcriptome in Turbot (Scophthalmus maximus L.) Intestine Following Vibrio anguillarum Infection - Chengbin Gao; Xin Cai; Qiang Fu; Ning Yang; Lin Song; Baofeng Su; Fenghua Tan; Baining Liu; Chao Li (Marine Biotechnology, 2019)

AKIP1 promotes angiogenesis and tumor growth by upregulating CXC-chemokines in cervical cancer cells - Wenying Zhang; Qiongwei Wu; Chao Wang; Longtao Yang; Ping Liu; Chengbin Ma (Molecular and Cellular Biochemistry, 2018)

The class D scavenger receptor CD68 contributes to mouse chronic liver injury - Le Yang; Lin Yang; Chengbin Dong; Liying Li (Immunologic Research, 2018)

Surface Enrichment and Depletion of the Active Ingredient in Spray Dried Amorphous Solid Dispersions - Zhen Chen; Kuan Yang; Chengbin Huang; Alan Zhu; Lian Yu; Feng Qian (Pharmaceutical Research, 2018)

Quantifying the spatial and temporal relationship between air and land surface temperatures of different land-cover types in Southeastern China - Yanling Sheng; Xiaoping Liu; Xuchao Yang; Qinchuan Xin; Chengbin Deng; Xia Li (International Journal of Remote Sensing, 2017)

BAC mediated transgenic Large White boars with FSHα/β genes from Chinese Erhualian pigs - Pan Xu; Qiuyan Li; Kai Jiang; Qiang Yang; Mingjun Bi; Chao Jiang; Xiaopeng Wang; Chengbin Wang; Longyun Li; Chuanmin Qiao; Huanfa Gong; Yuyun Xing; et al. (Transgenic Research, 2016)

Conservation and characterization of unique porcine interstitial telomeric sequences - GuangZhen Ji; Kai Liu; ChengBin Chen; WeiMin Ruan; Christina Glytsou; Yang Yang; Maja Okuka; WenQing Song; Sarantis Gagos; Ning Li; Lin Liu (Science China Life Sciences, 2012)